Kompetensi Kerja, Kecerdasan Emosional, Lingkungan Kerja Fisik Terhadap Kinerja Pegawai pada Dinas Pemadam Kebakaran dan Penyelamatan Kota Yogyakarta - Wisnu Utomo, Chandra; Herdiany, Hapsari Dyah; Wibowo, Frendy; Yosehana, Lina; Galuh, Aulia (Akmenika: Jurnal Akuntansi dan Manajemen, 2024)
The research results show that there is a positive and significant influence of work competency on employee performance at the Yogyakarta City Fire and Rescue Service. There is a positive and significant influence of emotional intelligence on the performance of Yogyakarta City Fire and Rescue Service employees. There is a positive and significant influence of the physical work environment on the performance of Yogyakarta City Fire and Rescue Service employees. There is a positive and significant influence of work competency, emotional intelligence, and physical work environment on the performance of Yogyakarta City Fire and Rescue Service employees.